PERANCANGAN CORPORATE IDENTITY RUMAH MAKAN SRI MELAYU PALEMBANG - Yosi Maryodi; Aji Windu Viatra; Muhammad Idris (UNIVERSITAS INDO GLOBAL MANDIRI, 2016)
Corporate Identity is a general overview of a medium to convey identity and inform about the positive values of a company, institution or government and private institution., The main objective of this scheme is to produce an identity design company that has its own characteristics. Sri Malay restaurant Palembang require designing new Corporate Identity to build corporate image. Through the creation of the logo on the Corporate Identity with unique simple impression and show the personality of the house eating, and then apply it in various media-related promotion.